EMPLOYMENT AND INCOME OF LABOR RETURNING FROM WORKING OVERSEA AT DONG KHE COMMUNE, DONG SON DISTRICT, THANH HOA PROVINCE - Thi Minh Ngoc, Vu; Thi Hoa, Le (Journal of Forestry Science and Technology, 2018)
Labor export activities bring many benefits such as reducing unemployment, increasing budget revenue, increasing income for laborers and improving the quality of life. However, this is only a temporary solution, not stable for workers. The paper first shows the number of workers moving oversea to work in recent years. Then, the situation of employment and income of labourers before moving oversea, during the period of working oversea and after returning home is analysed. In addition, the paper focuses on factors affecting the ability to find job and generate income of the labour. The most important factor is the laborers themselves. Workers’ demographic characteristic, working skill and willingness to find job are the factors affecting their employment situation most. On the other hand, some external factors also have impact on workers’ ability to find job, which are the concern of the authorities and the development of the region. Finally, the paper suggests that people after working oversea wishing to find a suitable job should identify their willingness to work and improve their working skills. The concerned agencies at all levels should pay more attention to the job creation for laborers after returning to the country.